Pterygium Excision with Sutureless, Glueless Conjunctival Autograft - Dhakal, Sachit; Thapa, Kamala; Sharan, Niranjan (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Pterygium is a common condition and various surgical techniques have been described for its excision, of which autografting is seen to have very less recurrence. Graft fixation with fibrin glue is gaining popularity, but autologous serum might be a cheaper alternative. This study was planned to explore the efficacy of autologous serum as a stabilising agent for graft surgery in pterygium. Methods: The hospital data of patients who underwent pterygium surgery with autografting using autologous serum in the Department of Ophthalmology of Shree Birendra Hospital, Chhauni, Kathmandu, Nepal between Oct 2015 to Sept 2017 were retrospectively analysed. The graft stability post-surgery was studied. Results: 46 eyes of 46 patients underwent pterygium surgery with autograft using autologous serum. The male to female ratio was 1.08:1, and the mean age was 45 years. All the pterygium were nasal sided. Post-operatively the graft was stable in all of the cases. Conclusions: Autologous serum is a good stabilising agent for graft surgery in pterygium.